Power and Persuasion: How to Command Success in Business and Your Personal Life by Michael Masterson and Agora - Masterson, Michael
Over these many years of watching Michael devour books on leadership, ask probing questions of all manner of leaders, and write his daily insights, I see now where it has all led--to a magnificent new book on leadership. If you are passionate about becoming a more effective leader, do yourself a favor and read Power and Persuasion